Pengolahan Sampah Kayu Menjadi Pupuk Organik: Pengabdian - Nyoman Dewi Pitaloka Cahyadi; Putu Ayu Trisna Febrianty (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Waste is an environmental problem that can disrupt the environment in Bresela Village. The purpose of this community service is to find ways to process waste in Bresela Village. This socialization is expected to provide knowledge and motivate the people of Bresela Village to actively process waste. This socialization also aims to help Bresela Village reduce waste from wood dust into fertilizer, thereby creating an integrated system between farmers and craftsmen This outreach program invited farmers and artisans from Bresela Village. The community service program was divided into two days. The first day was dedicated to outreach. Expert speakers were invited to present material on processing waste into organic fertilizer. The second day continued with practical sessions on processing waste from sawdust into organic fertilizer. This outreach program helped Bresela Village by providing solutions to the problems they faced. This outreach program helped farmers and artisans in Bresela Village establish an integrated system.